Praktik Sapa-Menyapa Kekerabatan (Studi Etnografi pada Masyarakat Dusun Cibitung, Kabupaten Cilacap) - Handuweni, Triesna; Supangkat, Budiawati; Mulyanto, Dede (Universitas Negeri Medan, 2024)
This research aimed to describe the diversity in the usage of kinship terms in relative address practice by Cibitung society, Karanggedang Village, Sidareja District, Cilacap Regency, Central Java. Qualitative methods with ethnographic design and data collection techniques of non-participatory observation, in-depth interviews, and literature studies were used to explore the terms of reference, term of address, kinship terms usage in kinship and non-kinship events, diversity of address terms and the underlying factors of that. Based on the field research results, it was found that in practice the term kinship can be used to greet relative and non-relative. Then, there are as many as 112 terms of address used to greet 19 categories of relative. This diversity is shown through differences in the application of kinship terms by the older generation (G+1, G+2) and the younger generation (G 0). Basically, the emergence of these various terms does not occur by itself, but is caused by several factors, such as: the development of the times, usage of other languages, social structures, migration culture, and exogamous marriages.